Mg(II)-Catechin nanoparticles delivering siRNA targeting EIF5A2 inhibit bladder cancer cell growth in vitro and in vivo. (March 2016) - Chen, Zhenhua; Yu, Ting; Zhou, Bangfen; Wei, Jinhuan; Fang, Yong; Lu, Jun; Guo, Ling; Chen, Wei; Liu, Zhi-Ping; Luo, Junhang
Abstract: Emerging evidence indicates that combination of two or more therapeutic strategies can synergistically enhance antitumor activity in cancer therapy. Here, we established a green method of generating nanocomposite particles that can be fabricated using catechin, a natural anti-cancer compound from green tea, and Mg 2+ in an easy one-step approach at room temperature. We show that Mg(II)-Catechin nanocomposite particles (Mg(II)-Cat NPs) have good biocompatibility and high cellular uptake also can load and effectively deliver small interfering RNA (siRNA) into cells in vitro and to tumor site in vivo . Mg(II)-Cat NPs by themselves had tumor-suppression effects. When complexed with siRNA that targets oncogene eukaryotic translation initiation factor 5A2 (EIF5A2), Mg(II)-Cat/siEIF5A2 complex had further enhanced anti-tumor activity. Mechanistically, we show that Mg(II)-Cat/siEIF5A2 inhibits oncogenic PI3K/Akt signal pathway. More importantly, Mg(II)-Cat/siEIF5A2 had tumor suppression effect in a clinically-relevant rat in-situ bladder cancer model. Our studies demonstrated that combination of Mg(II)-Cat NPs and siRNA is a promising therapeutic modality of combining chemotherapy with gene therapy in order to afford higher therapeutic efficacy and provided a proof of principle for such modality in a pre-clinical setting.